2021
DOI: 10.3389/fonc.2021.731989
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Serum Osteoprotegerin Level in Patients With Hepatocellular Carcinoma Following Surgical Resection

Abstract: BackgroundMultiple studies have reported that tissue or serum osteoprotegerin (OPG) level is a prognostic factor for patients with cancer. However, little is known about the role of serum OPG in hepatocellular carcinoma (HCC). In this study, we aimed to investigate whether serum OPG concentration has an effect on HCC patients’ prognosis.MethodsA total of 386 eligible HCC patients undergoing radical hepatectomy were enrolled from Shanghai Ninth People’s Hospital and Zhongshan Hospital between 2010 and 2018. Kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Interestingly, genetic deletion of TNFRSF11A in thymic epithelial cells resulted in impaired thymic involution and blunted expansion of natural regulatory T (Treg) cells [ 43 ]. Additionally, study showed that HCC patients with high serum TNFRSF11B, also known as osteoprotegerin (OPG), level had poorer survival rates compared with HCC patients with low OPG level [ 44 ]. CD40 ligand-expressing dendritic cells could induce regression of HCC [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, genetic deletion of TNFRSF11A in thymic epithelial cells resulted in impaired thymic involution and blunted expansion of natural regulatory T (Treg) cells [ 43 ]. Additionally, study showed that HCC patients with high serum TNFRSF11B, also known as osteoprotegerin (OPG), level had poorer survival rates compared with HCC patients with low OPG level [ 44 ]. CD40 ligand-expressing dendritic cells could induce regression of HCC [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR examination of tumor tissues and paracancerous tissues from 40 patients with liver cancer revealed that TNFRSF11B was highly expressed in liver cancer tissues 49 . A report found that HCC patients with high TNFRSF11B expression had a lower survival rate and that TNFRSF11B was an independent risk factor for HCC 50 . Patients with increased TNFRSF11B expression in malignancies such as oral squamous cell carcinoma and prostate cancer have a worse prognosis 48 .…”
Section: Disscussionmentioning
confidence: 99%
“…Real-time PCR examination of tumor tissues and paracancerous tissues from 40 patients with liver cancer revealed that TNFRSF11B was highly expressed in liver cancer tissues 53 . A report found that HCC patients with high TNFRSF11B expression had a lower survival rate and that TNFRSF11B was an independent risk factor for HCC 54 . Patients with increased TNFRSF11B expression in malignancies such as oral squamous cell carcinoma and prostate cancer have a worse prognosis 52 .…”
Section: Disscussionmentioning
confidence: 99%